EFFICACY AND SAFETY OF METOPROLOL SUCCINATE IN HIGH DOSES IN PATIENTS WITH STABLE COURSE OF ISCHEMIC HEART DISEASE - S. N. Tolpygina; S. Y. Martsevich (Столичная издательская компания, 2016)
Aim. To compare two initial doses (50 or 100mg/day) ofmetoprolol succinate in control released presentation (Betaloc ZOK, AstraZeneca) for achievement of target level of heart rate (HR) in patients with stable course of ischemic heart disease (IHD).Material and methods. 50 patients (34 men and 16 women, aged 61,3 y.o., in average) with IHD were involved into the open randomized comparative study. IHD duration was from 1 to 22 years (8,3 years in average). 47 patients completed study, 3 patients drop out because of side effects. Previous therapy with β-blockers or other HR reducing drugs was replaced on metoprolol. Patients were randomized in 2 groups (G1 and G2). The initial metoprolol dose was 50 mg in G1 patients and 100 mg - in G2 patients. The dose was enlarged twice if necessary. Study duration was 6 weeks. The change of HR, blood pressure, electrocardiogram parameters was evaluated. Patients filled in Seattle angina questionnaire initially and after 6 weeks treatment. Therapy tolerability was also estimated.Results. In 6 weeks of therapy 61% of G1 patients and 87,5% of G2 patients (p<0,01) reached HR target. Dependence of achievement of target HR and dose of metoprolol was observed (r=0,3; p=0,056). Improvement of the HR control was accompanied by reduction of frequency of angina attacks and increase of life quality.Conclusion. Metoprolol (Betaloc ZOK) 200 mg/day provides more effective HR control in patients with IHD vs metoprolol 50-100 mg/day and has good tolerability.